Consciousness, emotional self-regulation, and the brain - Beauregard, Mario (Advances in consciousness research ;, 2004)
During the last decade, the study of emotional self-regulation has blossomed in a variety of sub-disciplines belonging to either psychology (developmental, clinical) or the neurosciences (cognitive and affective). Consciousness, Emotional Self-Regulation and the Brain gives an overview of the current state of this relatively new scientific field. Several areas are examined by some of the leading theorists and researchers in this emerging domain. Most chapters seek to either present theoretical and developmental perspectives about emotional self-regulation (and dysregulation), provide cutting e.